PERANCANGAN E-COMMERCE BERBASIS WEBSITE PADA UMKM "BUNCH OF GIFTS" - Nathanael Boan Tua Sipahutar (2023)
MSME "Bunch of Gifts" is an MSME located in Jakarta that sells products in the form of handicrafts and souvenirs. This MSME has not utilized information technology in its business processes, where the sales process is still carried out conventionally by offering it to friends, so that sales of handicrafts and souvenirs are still limited around the South Jakarta area. Promotional methods used are still limited to brochures and mouth to mouth. It was recorded in the sales report that the MSME "Bunch of Gifts" experienced a decrease in purchase transactions by 25.7% by comparing the total turnover in June 2019 with June 2021 for the snack bouquet product. In addition, the MSME's find it difficult to collect sales data every month due to still using the manual method which has the risk of losing sales data due to human error. In this study, researchers used the waterfall method and also used codeigniter as an application development framework supported by a MySQL database. Researcher use the waterfall method because it is systematic and can reduce the possibility of problems occurring. This study aims to design a web-based e-commerce information system to expand the marketing reach of MSME and digitize existing business processes. From the research results it is known that e-commerce design makes it easier for MSME to provide product information to customers, expand market share which can increase sales and simplify the process of recording sales transactions.